Human capital, social capital, psychological capital, and job performance: Based on fuzzy-set qualitative comparative analysis - Xu, Qian; Hou, Zhe; Zhang, Chao; Yu, Feng; Guan, Jiangyue; Liu, Xiao (Frontiers in Psychology, 2022)
The present study investigated the configuration effect of human capital, social capital, and psychological capital on job performance. Human capital questionnaire, social capital scale, psychological capital, and job performance scale were used to survey 458 employees. Results revealed that high task-oriented psychological capital and high guanxi-oriented psychological capital were required for high job performance. Also, the “plural concurrency” of human, social, and psychological capital led to a diverse configuration of high job performance, i.e., the driving path of high work performance had the characteristics of “same destination by different paths”.